Factors Affecting the Outcome of Multiple Intracranial Aneurysm Surgery - Abdallah, Anas; Asiltürk, Murad; Emel, Erhan; Güler Abdallah, Betül (Indian Journal of Neurosurgery, 2018)
Objectives Multiple intracranial aneurysms (MIAs) are fairly common entities. Unless MIAs are incidentally diagnosed, they remain asymptomatic until they rupture. In this study, the authors investigated factors affecting the surgical outcomes in patients with MIA by evaluating the surgical outcomes of 90 consecutive cases.Material and Methods Medical records were retrospectively reviewed for 409 consecutive cerebral aneurysm cases that underwent surgery in the hospital from 2011 to 2013. The patients’ data were prospectively collected. All MIA patients (n = 90) constituted the core sample for this study.Results The authors detected 221 aneurysms in 90 patients (49 females and 41 males; mean age: 50.8 ± 11.9 years; range: 25–82 years). Of the patients, 67 presented with subarachnoid hemorrhage, whereas 23 were incidentally diagnosed with unruptured aneurysms. The mortality rate was 13.3% (n = 12). The morbidity rate was 18.8% (n = 17). Of the patients, 67.8% (n = 61) had returned to their jobs and normal daily activities by their last follow-up (average: 52.3 months). History of coronary artery diseases (CADs) and low neurologic grade at presentation (Hunt-Hess grade 4/5) are independent risk factors for increasing morbidity and mortality in patients with MIA (odds ratio [OR]: 18.46; p = 0.007); (OR: 30.0; p = 0.002) and (OR: 0.06; p = 0.0001); (OR: 0.07; p = 0.002), respectively.Conclusion History of CADs and high Hunt-Hess grade are independent risk factors for poor surgical outcomes of patients with MIA.
Keywords: clipping microsurgical; coronary artery disease; multiple intracranial aneurysm